Safety and Efficacy of Inclisiran in Hyperlipidemia: An Updated Meta‐Analysis of Randomised Controlled Trials - Jawad Basit (19231376) (2025)
Introduction Inclisiran, a small interfering RNA (siRNA), reduces the levels of low‐density lipoproteins (LDL) in the body by preventing the hepatic synthesis of proprotein convertase subtilisin/kexin type 9 (PCSK9). However, there is limited pooled data regarding the efficacy and safety of inclisiran in patients with hypercholesterolemia. Methods PubMed/MEDLINE, Embase and the Cochrane Library were searched by investigators from inception till July 2024 to identify randomised controlled trials (RCTs) that investigated inclisiran in patients with hypercholesterolemia. Weighted mean differences (MDs) for continuous outcomes and risk ratios (RRs) for the dichotomous outcomes were pooled. The analysis was conducted using the random effects model, and a p‐value of < 0.05 was considered statistically significant. Results A total of 8 RCTs reporting data for 5016 patients were included in the pooled analysis. Our pooled analysis demonstrated that inclisiran was associated with a significant decline in the % of LDL‐C levels (MD = −50.42, 95% CI: −56.15 to −44.70), % of PCSK9 levels (MD = −78.57, 95% CI: −81.64 to −75.50), % of total cholesterol levels in the body (MD = −31.22, 95% CI: −33.08.15 to −29.37), and apo B levels (MD = −41.47, 95% CI: −44.83 to −38.11) when compared with the control group. The risk of all‐cause death, cardiovascular death, major adverse cardiovascular events, myocardial infarction, stroke, and serious adverse events remained comparable (p > 0.05) across the two groups. Conclusion Inclisiran reduces LDL‐C, PCSK9, cholesterol and apo‐B levels in the body without increasing the risk of serious adverse events. Other Information Published in: Endocrinology, Diabetes & Metabolism License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/edm2.70039